2016
DOI: 10.1007/s11356-016-8272-y
|View full text |Cite
|
Sign up to set email alerts
|

Field evidence of bird poisonings by imidacloprid-treated seeds: a review of incidents reported by the French SAGIR network from 1995 to 2014

Abstract: The large-scale use of neonicotinoid insecticides has raised growing concerns about their potential adverse effects on farmland birds, and more generally on biodiversity. Imidacloprid, the first neonicotinoid commercialized, has been identified as posing a risk for seed-eating birds when it is used as seed treatment of some crops since the consumption of a few dressed seeds could cause mortality. But evidence of direct effects in the field is lacking. Here, we reviewed the 103 wildlife mortality incidents repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(111 citation statements)
references
References 50 publications
4
91
1
2
Order By: Relevance
“…Millot et al (2015) reported that about 10% of the grey partridges found in their study fields that were exposed to thiacloprid, subsequently died, even though few direct impacts of other pesticides were detected. Finally, Millot et al (2017) suggested that in France, mortality due to poisoning by imidacloprid-treated seeds was at least likely in 70% of wildlife mortality incidents reported during 1994-2014. Lopez-Antia et al (2016 conclude that the use of pesticide-treated seeds presents an unacceptable risk to farmland birds.…”
Section: Studies In the Natural Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Millot et al (2015) reported that about 10% of the grey partridges found in their study fields that were exposed to thiacloprid, subsequently died, even though few direct impacts of other pesticides were detected. Finally, Millot et al (2017) suggested that in France, mortality due to poisoning by imidacloprid-treated seeds was at least likely in 70% of wildlife mortality incidents reported during 1994-2014. Lopez-Antia et al (2016 conclude that the use of pesticide-treated seeds presents an unacceptable risk to farmland birds.…”
Section: Studies In the Natural Environmentmentioning
confidence: 99%
“…One study estimated that the daily doses of insecticides ingested by red-legged partridges could cause sublethal (imidacloprid) or even lethal (fipronil) effects (Lopez-Antia et al 2016). A second concluded that mortality due to poisoning by imidacloprid-treated seeds was at least likely in 70% of reported wildlife mortality incidents (Millot et al 2017). Evidence of the indirect, food chain effects of these insecticides remains rare, though one correlative study found that some local populations of insectivorous birds declined more in areas with higher surface water concentrations of imidacloprid, possibly as a consequence of reduced invertebrate food supplies (Hallmann et al 2014).…”
Section: Summary Of Impacts On Vertebratesmentioning
confidence: 99%
“…Aside from evidence of mild trauma, no other significant findings were observed during postmortem examination, and strychnine was not detected in digestive contents or liver tissues. Previous reports of imidacloprid-related mortality in birds have involved granivorous species and the ingestion of imidacloprid-treated seeds either during sowing or after accidental spills (Millot et al 2017). The route of exposure for the birds examined in the present study is likely ingestion of natural seeds contaminated during the drench application.…”
Section: Discussionmentioning
confidence: 74%
“…Previous reports of imidacloprid‐related mortality in birds have involved granivorous species and the ingestion of imidacloprid‐treated seeds either during sowing or after accidental spills (Millot et al ). The route of exposure for the birds examined in the present study is likely ingestion of natural seeds contaminated during the drench application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation